Pathophysiological Mechanisms Linking Myocardial Infarction to Cardiac Arrest: A Literature Review - Andi Suleha; Akina Maulidhany Tahir; Fadillah Maricar; Priscilla Sasmita Rido; Nurhikmawati Nurhikmawati (PSPP JOURNALS, 2026)
Myocardial infarction (MI) is a leading cause of cardiac arrest and sudden cardiac death worldwide. The pathophysiological link involves complex interactions between cellular, electrophysiological, hemodynamic, and neurohormonal mechanisms. The objective of the research to comprehensively review the pathophysiological mechanisms linking myocardial infarction to cardiac arrest. The methods of the research was a descriptive-analytic literature review was conducted using PubMed, ScienceDirect, SpringerLink, and Google Scholar databases (2021–2025). Study selection followed PRISMA guidelines. The results of the showed that eight studies were included. Key mechanisms include myocardial ischemia leading to ATP depletion and acidosis, ionic imbalance, arrhythmogenic substrate formation, sympathetic overactivation, inflammatory response and oxidative stress, and hemodynamic collapse. Cardiac arrest following MI is primarily driven by fatal ventricular arrhythmias and pump failure. Understanding these mechanisms is essential for improving prevention and management strategies.